Rock strength and structural controls on fluvial erodibility: Implications for drainage divide mobility in a collisional mountain belt - Zondervan, Jesse R.; Stokes, Martin; Boulton, Sarah J.; Telfer, Matt W.; Mather, Anne E. (Earth and planetary science letters, 2020)
•We estimate rock strength, erodibility and drainage divide mobility in the High Atlas Mountains.•The weakest rock-type in the High Atlas is up to two orders of magnitude more erodible than the strongest.•In gently deformed horizontal strata of the sedimentary cover the drainage divide is mobile.•Faulted and folded metamorphic sedimentary bedrock coincide with a stable drainage divide.•Exhumation of crystalline basement forces the drainage divide into the centre of exposed basement. Numerical model simulations and experiments have suggested that when migration of the main drainage divide occurs in a mountain belt, it can lead to the rearrangement of river catchments, rejuvenation of topography, and changes in erosion rates and sediment flux. We assess the progressive mobility of the drainage divide in three lithologically and structurally distinct groups of bedrock in the High Atlas (NW Africa). The geological age of bedrock and its associated tectonic architecture in the mountain belt increases from east to west in the study area, allowing us to track both variations in rock strength and structural configuration which influence drainage mobility during erosion through an exhuming mountain belt. Collection of field derived measurements of rock strength using a Schmidt hammer and computer based extraction of river channel steepness permit estimations of contrasts in fluvial erodibilities of rock types. The resulting difference in fluvial erodibility between the weakest and the strongest lithological unit is up to two orders of magnitude. Published evidence of geomorphic mobility of the drainage divide indicates that such a range in erodibilities in horizontal stratigraphy of the sedimentary cover may lead to changes in erosion rates as rivers erode through strata, leading to drainage divide migration. In contrast, we show that the faulted and folded metamorphic sedimentary rocks in the centre of the mountain belt coincide with a stable drainage divide. Finally, where the strong igneous rocks of the crystalline basement are exposed after erosion of the covering meta-sediments, there is a decrease in fluvial erodibility of up to a factor of three, where the drainage divide is mobile towards the centre of the exposed crystalline basement. The mobility of the drainage divide in response to erosion through rock-types and their structural configuration in a mountain belt has implications for the perception of autogenic dynamism of drainage networks and fluvial erosion in mountain belts, and the interpretation of the geomorphology and downstream stratigraphy.